Rejection of Radical Nationalism in Wartime Yugoslavia: The Case of Tuzla (1990–1995). Issue 3 (2nd September 2018) - Filic, Goran
Abstract: The article identifies causal mechanisms that help explain why the city of Tuzla managed to reject and avoid inter-ethnic conflict and radical nationalism during the wars of the 1990s in the former Yugoslavia. Despite the overwhelming odds of being surrounded by vicious ethnic fighting and relentless nationalist attacks, the city of Tuzla protected and sustained peace in its borders. This research provides some explanations as to why Tuzla managed to survive radical nationalism and fragmentation during the disintegration of the former Yugoslavia. The article concludes that Tuzla's success was path dependent and its ability to reject violent nationalism revolved around Tuzla's identity of traditionally working class, anti-nationalist, anti-fascist forces around which Tuzla's citizens rallied. This helped elect the only non-ethnic political leadership in the country during the first multiparty municipal elections, and also actively protected citizens' democratic choice against nationalist attempts to foster ethnic mobilisation and ethnic violence.